Evaluation of a Continuous Laser Ablation Coating Removal Device for Steel Bridges. Issue 5 (May 2022) - Provines, Jason; Rickard, Raquel; Sharp, Stephen
One common method for removing deteriorated coatings from steel bridges is abrasive blast cleaning. Although effective, abrasive blast cleaning can be hazardous to operators and must be conducted using expensive containment. One innovative solution to the hazardous nature and high expense of blast cleaning is laser ablation coating removal (LACR). LACR uses a high-energy laser, rather than conventional blasting, to remove the coating and has the potential to minimize operator hazards and eliminate the need for containment. The purpose of this study was to evaluate a continuous LACR system in relation to its coating removal effectiveness, industrial hygiene (IH), and effect on the steel substrate below the underlying coating. Coating removal and IH evaluation were performed on coated steel samples, including some with lead and other toxic metal coatings. LACR was also performed on bare steel, used to perform mechanical testing, such as tension, fatigue, hardness, and microstructural analysis to evaluate the effect of LACR on a steel substrate. In comparison to the pulsed LACR system evaluated in a previous study, the continuous LACR system was 2–27 times faster at removing most coatings, but it was unable to remove white coatings like the pulsed LACR system was able to do. IH evaluation showed that the continuous LACR system was likely to generate toxic metal fumes when ablating lead coatings, but this could possibly be minimized by designing an attached fume extraction system. Mechanical testing showed that the continuous LACR had no detrimental effects to the steel substrate.